A Four‐Diode Full‐Wave Ionic Current Rectifier Based on Bipolar Membranes: Overcoming the Limit of Electrode Capacity. (26th May 2014) - Gabrielsson, Erik O.; Janson, Per; Tybrandt, Klas; Simon, Daniel T.; Berggren, Magnus
<x xml:space="preserve">Abstract</x> Full‐wave rectification of ionic currents is obtained by constructing the typical four‐diode bridge out of ion conducting bipolar membranes. Together with conjugated polymer electrodes addressed with alternating current, the bridge allows for generation of a controlled ionic direct current for extended periods of time without the production of toxic species or gas typically arising from electrode side‐reactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>